Developmental dysplasia of the hip: usefulness of next generation genomic tools for characterizing the underlying genes – a mini review. Issue 1 (4th March 2016) - Basit, S.; Hannan, M. A.; Khoshhal, K. I.
Abstract : Developmental dysplasia of the hip (DDH) is one of the most common skeletal anomalies. DDH encompasses a spectrum of the disorder ranging from minor acetabular dysplasia to irreducible dislocation, which may lead to premature arthritis in later life. Involvement of genetic factors underlying DDH became evident when several studies reported chromosomal loci linked to DDH in families with multiple affected individuals. Moreover, using association studies, variants in genes involved in chondrogenesis and joint formation have been shown to be associated with DDH. At least, one study identified a pathogenic variant in the chemokine receptor gene in DDH. No genetic analysis has been reported or carried out in DDH patients from the Middle East. Here, we review the literature related to genetics of DDH and emphasized the usefulness of new generation technologies in identifying genetic variants underlying DDH in consanguineous families. Abstract :